Inovasi Website IKI Pesat Jatim (Inisiatif, Kolaborasi, dan Inovasi Pesantren Sehat Jawa Timur) Sebagai Upaya Peningkatan Pelayanan Kesehatan (Studi Kasus di Kabupaten Sidoarjo) - Adreansyah, Dimas; Eprilianto, Deby Febriyan (Madani: Jurnal Ilmiah Multidisiplin, 2025)
In this study uses a qualitative approach where the researcher describes the results of the study and explain with a clear description regarding the innovation of the website IKI PESAT JATIM (Initiative, Collaboration and Innovation Pesantren Sehat East Java) as an effort to improve health services. The data in this study were collected through interviews, observations, and documentation. In this study using purposive sampling technique, i.e. sampling technique based on specific considerations of the researcher, where informants were purposively selected as they were judged to have direct knowledge and involvement in the implementation of the IKI PESAT JATIM program. The instruments of this study were the researcher himself, the interview guide, a notebook, and a smartphone as both a voice recorder and a camera as documentary evidence. Data analysis started from data reduction, data presentation, and drawing conclusions. The results of the study show the analysis conducted by the researcher regarding the innovation of the website IKI PESAT JATIM in Sidoarjo Regency, it can be concluded that IKI PESAT JATIM has provided ease in health reporting so as to support the training and improvement of health services in the environment of East Java boarding schools.